Coarse graining, dynamic renormalization and the kinetic theory of shock clustering. (4th February 2016) - Li, Xingjie; Williams, Matthew O; Kevrekidis, Ioannis G; Menon, Govind
Abstract: We demonstrate the utility of the equation-free methodology developed by one of the authors (IGK) for the study of scalar conservation laws with disordered initial conditions. The numerical scheme is benchmarked on exact solutions in Burgers turbulence corresponding to Lévy process initial data. For these initial data, the kinetics of shock clustering is described by Smoluchowski's coagulation equation with additive kernel. The equation-free methodology is used to develop a particle scheme that computes self-similar solutions to the coagulation equation, including those with fat tails.